The march : the story of the greatest march in American history / [videorecording (DVD)] - Akomfrah, John; Washington, Denzel, 1954-; Belafonte, Harry, 1927-; Baez, Joan; Jones, Clarence B., 1931-; Mudd, Roger, 1928-2021-; Winfrey, Oprah (PBS Distribution, 2013)
Witness the compelling and dramatic story of the 1963 March on Washington, where Dr. Martin Luther King gave his stirring "I Have a Dream" speech. This watershed event in the Civil Rights Movement helped change the face of America. Recounts the events when 250,000 people came together to form the largest demonstration the young American democracy had ever seen.